2016
DOI: 10.5194/isprs-annals-iii-8-159-2016
|View full text |Cite
|
Sign up to set email alerts
|

Overland Flow Analysis Using Time Series of Suas-Derived Elevation Models

Abstract: ABSTRACT:With the advent of the innovative techniques for generating high temporal and spatial resolution terrain models from Unmanned Aerial Systems (UAS) imagery, it has become possible to precisely map overland flow patterns. Furthermore, the process has become more affordable and efficient through the coupling of small UAS (sUAS) that are easily deployed with Structure from Motion (SfM) algorithms that can efficiently derive 3D data from RGB imagery captured with consumer grade cameras. We propose applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Gully erosion rates and evolution can be monitored in the field or modeled on the computer. Field methods include dendrogeomorphology (Malik, 2008) and permanent monitoring stakes for recording erosion rates, extensometers for recording mass wasting events, weirs for recording water and suspended sediment discharge rates, and time series of surveys using total station theodolites (Thomas et al, 2004), unmanned aerial systems (UASs) (Jeziorska et al, 2016;Kasprak et al, 2019;Yang et al, 2019), airborne lidar (Perroy et al, 2010;Starek et al, 2011), and terrestrial lidar (Starek et al, 2011;Bechet et al, 2016;Goodwin et al, 2016;Telling et al, 2017). With terrestrial lidar, airborne lidar, and UAS photogrammetry, there are now sufficient-resolution topographic data to morphometrically analyze and numerically model fine-scale landscape evolution in GIS, including processes such as gully formation and the development of microtopography.…”
Section: Introductionmentioning
confidence: 99%
“…Gully erosion rates and evolution can be monitored in the field or modeled on the computer. Field methods include dendrogeomorphology (Malik, 2008) and permanent monitoring stakes for recording erosion rates, extensometers for recording mass wasting events, weirs for recording water and suspended sediment discharge rates, and time series of surveys using total station theodolites (Thomas et al, 2004), unmanned aerial systems (UASs) (Jeziorska et al, 2016;Kasprak et al, 2019;Yang et al, 2019), airborne lidar (Perroy et al, 2010;Starek et al, 2011), and terrestrial lidar (Starek et al, 2011;Bechet et al, 2016;Goodwin et al, 2016;Telling et al, 2017). With terrestrial lidar, airborne lidar, and UAS photogrammetry, there are now sufficient-resolution topographic data to morphometrically analyze and numerically model fine-scale landscape evolution in GIS, including processes such as gully formation and the development of microtopography.…”
Section: Introductionmentioning
confidence: 99%
“…We address the first issue by reconstructing bare earth from two UAS surveys acquired in The UAS data were interpolated from the point clouds to 0.3 meter resolution rasters. The details of the data acquisition and processing of the UAS-based DEMs are provided by Jeziorska et al [18]. Lidar data used in this study were collected by the North Carolina Floodplain Mapping Program [19] in 2015 as part of a statewide survey, with average point density of 3 points per square meter and multiple return classified points.…”
Section: Updating Lidar-based Dem With Uas-based Dsmsmentioning
confidence: 99%
“…As a result of the model calibration, it can be subsequently concluded that a photogrammetrically derived DTM from a UAS point cloud is effective in modeling flow. Jeziorska et al, [30] reported that a UAS derived terrain model is more effective in accounting for flow morphology and patterns over a lidar derived DTM in areas not covered by vegetation because of its increased spatial resolution. We attribute the slightly lower values of R, E, and d in the UAS derived terrain model to the uncertainty in interpolated terrain beneath the few areas within the watershed that are covered by trees and shrub and also to the single flow (D-8) algorithm used by SWAT.…”
Section: Model Calibration and Validation At The Uas Spatial Scalementioning
confidence: 99%
“…Quite recently, photogrammetrically derived DSM and DTM from high resolution UAS imagery has been emerging in the hydrologic literature [18,[26][27][28]. Photogrammetrically derived UAS data has been used to model surface flow within and outside urban areas [17,29,30], spatial and temporal variability of riverbed hydraulic conductivity [31], channel morphology [32], streambank topography [33], streambank erosion [27], and gully erosion in agricultural and urban watersheds [34,35]. Stocker [34] demonstrated that the photogrammetrically derived data from UAS can measure gully erosion in farmland in a way that LiDAR technology could not due to the increased spatial and temporal resolution that UAS models provide.…”
Section: Introductionmentioning
confidence: 99%